Employing Fuzzy-weighted SERVQUAL, Refined-KANO, IPA, and QFD to Assess Service Quality in Vocational Higher Education - Surtiningtyas, Sri Rahayu; Saputra, Surya Tri (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This research aims to evaluate the quality of vocational higher education services and determine which characteristics most influence service quality. The research used multiple service quality methods, including Fuzzy Weighted SERVQUAL, Refined Kano, Importance-Performance Analysis, and Quality Functional Deployment. This study was conducted in 7 aviation polytechnics: Indonesian Aviation Polytechnic Curug, Medan Aviation Polytechnic, Palembang Aviation Polytechnic, Surabaya Aviation Polytechnic, and Makassar Aviation Polytechnic, and Aviation Polytechnic Jayapura under the Human Resources Development Centre for Air Transportation - Ministry of Transportation. Random sampling was used to determine the number of samples. The population was 3063 cadets, with 507 samples drawn from seven Aviation Polytechnics in Indonesia. The research instrument was a questionnaire with Servqual dimensions and attributes that meet two criteria: service quality Servqual includes five dimensions and attributes of service quality in vocational higher education comprising 23 attributes. The data analysis techniques used were both quantitative and qualitative. The results of this study found that; (1) Of the 23 service quality items at vocational colleges, 14 items are the voice of customers for the Cadets of the seven aviation polytechnics under the PPSDMPU with modern or up-to-date practice lab equipment as the most item that needed to be improved. (2) Formulate 22 alternative technical problem-solving sequentially according to priority with the fulfillment of items carried out by considering the capability of the resources owned by each aviation polytechnic with the application of rights and obligations to all learners as the most quality characteristics that should be implemented.